Bensulfuron-methyl resistant Sagittaria trifolia L.: multiple resistance, cross-resistance and molecular basis of resistance to acetolactate synthase-inhibiting herbicides - Fu, Danni; Shafi, Jamil; Zhao, Bochui; Li, Xiuwei; Zhu, He; Wei, Songhong; Ji, Mingshan (Archives of Biological Sciences, 2017)
Acetolactate synthase (ALS)-inhibiting herbicides play an important role in controlling broad-leaved weeds. Populations of Sagittaria trifolia L. showed resistance to ALS-inhibiting sulfonylurea herbicides (e.g. bensulfuron-methyl) in paddy fields in the northeast of China. In our study, whole-plant bioassays were performed on eight suspected resistant S. trifolia populations that showed high levels of resistance to bensulfuron-methyl, with resistance indices from 31.06 to 120.35. The results of ALS-activity assays were consistent with the observed whole-plant dose-response data. This confirmed that resistant populations displayed significantly higher ALS activity than the sensitive population due to prevention of normal enzyme-herbicide interaction. The mutations Pro-197-Ser, Pro-197-His, Pro-197-Thr and Pro-197-Leu were identified in the ALS gene of resistant populations. Pro-197-His and Pro-197-Thr mutations conferring resistance to bensulfuron-methyl are reported for the first time in S. trifolia. All resistant populations were resistant to sulfonylurea (SU) herbicides, but not to imidazolinone (IMI) herbicides. HLJ-5 and JL-3 populations were resistant to bispyribac-sodium of the pyrimidinyl-thiobenozoate (PTB) class of ALS herbicides, JL-2 to penoxsulam of triazolopyrimidine (TP) class and JL-1 to pyribenzoxim, also of PTB class. The eight S. trifolia populations were susceptible to other herbicide modes of action tested. https://doi.org/10.2298/ABS170210010F Received: February 10, 2017; Revised: March 6, 2017; Accepted: March 9, 2017; Published online: March 20, 2017 How to cite this article: Fu D, Shafi J, Zhao B, Li X, Zhu H, Wei S, Ji M. Bensulfuron-methyl resistant Sagittaria trifolia L.: Multiple resistance, cross-resistance and molecular basis of resistance to acetolactate synthase-inhibiting herbicides. Arch Biol Sci. 2017;69(4):649-58.